THE EXTRACT SOYBEAN OF LOCAL VARIETIES AS REDUCE ADVANCED GLYCATION END PRODUCTS AND HEMOGLOBIN A1C IN TYPE 2 DIABETES MICE - Christyaningsih, Juliana; Taufiqurrahman, Taufiqurrahman; Sujono, Sujono (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: Glucose and amino acids or fat in diabetic patients if were oxidized to form a compound amadori product (hemoglobin A1c [HbA1c]) and intermediate dicarbonyl that uses reactive carbonyl groups to bind with the amino acids to form advanced glycation end products (AGEs). Soybean is classified as a low index glycemic and content of polyphenol compounds are reported to have various biological activities, which are beneficial to health. Project objectives: The aim of this study was to determine the effect of extract soybean of local varieties obtained on AGEs and HbA1c. Methods: This study was a randomized pretest-posttest control group design. The amount of 28 Mus musculus Balb/C was divided into seven groups. The control group was divided four, while the test group was given extracts of three varieties of soybean, that is, Gema, Wilis, and Argomulyo at a dose equivalent to 1 g of soy/kg BW/day for 25 days. Type 2 diabetes (T2D) mice made with the administration of STZ at a dose of 55 mg/kg in mice. Results: There is a sign of differences in HbA1c levels in the group of mice, and there are different levels of AGEs, though not statistically significant in the group of mice. Conclusions: The extract soybean was a positive effect on the levels of AGEs and HbA1c in T2D mice.